Are professors worth it? The value-added and costs of tutorial instructors - Jan Feld; Nicolás Salamanca; Ulf Zölitz (University of Zurich, Department of Economics, 2018)
A substantial share of university instruction happens in tutorial sessions - small group instruction given parallel to lectures. In this paper, we study whether instructors with a higher academic rank teach tutorials more effectively in a setting where students are randomly assigned to tutorial groups. We find this to be largely not the case. Academic rank is unrelated to students' current and future performance and only weakly positively related to students' course evaluations. Building on these results, we discuss different staffing scenarios that show that universities can substantially reduce costs by increasingly relying on lower-ranked instructors for tutorial teaching.
Keywords: I21; I24; J24; 330; Teacher value-added; teaching effectiveness; higher education